Some remarks about the reception of Maria Pawlikowska-Jasnorzewska’s works in the “Russophone space” - Bednarczyk, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
Within the framework of the studies concerning the reception of Maria Pawlikowska-Jasnorzewska’s poetry in the Soviet Union and in Russia, the author explores the issue of the political context in the target cultural and linguistic space. She also explores the problem of literal translation as a method of popularising the poems studied, and analyses the function of the Russophone Internet in the popularisation of the Polish poet.